Pernicious anemia is a common cause of cobalamin deficiency-caused megaloblastic anemia in Hainan, China - Meixiao Shen; Xiansheng Luo; Cuiyun Wu; Juan Wang; Zhiming Wang; Meiqing Lei (Hematology)
Background Pernicious anemia (PA) is believed to be highly prevalent in Western countries but has rarely been reported in China. The study explores whether PA, an autoimmune disease, is an uncommon cause of cobalamin (vitamin B12) deficiency anemia in China.Methods Clinical and hematological data were collected from 90 cobalamin deficiency-caused megaloblastic anemia (MA) patients between July 2014 and December 2021. Through anti-intrinsic factor antibody (IFA) and anti-parietal cell antibody (PCA) testing, PA was distinguished from other causes of cobalamin deficiency leading to MA. Meanwhile, 30 healthy controls (HCs) were included to estimate the positive rates of IFA and PCA.Results Of the 30 HCs, only one tested positive for IFA, and all 30 tested negative for PCA. Among the 90 patients with cobalamin deficiency-caused MA, 76.7% were positive for IFA, and 47.8% were positive for PCA; a total of 76 patients (84.4%) were diagnosed with PA. The mean follow-up time was 41.0 ± 16.3 months. During the follow-up period, no case relapsed among the continuous cobalamin-supply treatment patients, while 24.4% of patients relapsed due to the interruption of maintenance cobalamin-supplement therapy (the median recurrence time was 54.0 ± 17.7 months).Conclusions The proportion of PA in cobalamin deficiency-caused MA patients in Hainan province was higher than 80%, which was more common than expected. Therefore, screening for IFA, PCA, endoscopic biopsy, and thyroid-related parameters are recommended for all cobalamin deficiency-caused MA patients. Furthermore, maintenance cobalamin-supplement therapy is important for PA patients.